Vaccination, infection, and hybrid immunity: determinants of SARS-CoV-2 IgG antibody levels and protection in Quzhou, China - Yin, Zhiying; Yin, Mengcheng; Zhao, Fei; Fu, Canya; Xu, Wenjie; Fang, Quanjun; Gong, Xiaoying; Cao, Guoping; Zheng, Canjie (Frontiers in Immunology, 2025)
ObjectivesTo investigate the factors influencing SARS-CoV-2 IgG antibody levels and protection in a population that has experienced both vaccination and COVID-19 infections, predominantly caused by the Omicron BA.5.2 and BF.7 variants.MethodsAnti-SARS-CoV-2 IgG antibody levels were measured using chemiluminescent microparticle immunoassay (CMIA). Multivariate regression analyses assessed factors influencing antibody levels, and decision tree models predicted variable priorities.ResultsAmong the 3494 participants, the median (IQR) anti-SARS-CoV-2 IgG level was 396.53 (280.51–471.03) AU/mL, with a seropositive rate of 97.28%. Multivariate analysis revealed that vaccination status, infection status, residence county, occupation, and vaccination interval were significantly associated with antibody concentration. The decision tree model indicated that vaccination had a greater effect on antibody concentration than infection, while infection had a stronger impact on seropositivity. The Breakthrough Infection group had the highest antibody concentration compared with other groups.ConclusionsVaccination and infection were identified as the primary determinants of SARS-CoV-2 IgG antibody levels, with hybrid immunity significantly enhancing antibody responses. New evaluation methods or revised detection thresholds were needed to better assess population immunity.